2012
DOI: 10.2105/ajph.2011.300431
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in HIV Diagnoses Among Persons Aged 50 Years and Older in 37 US States, 2005–2008

Abstract: Racial/ethnic disparities in HIV diagnosis rates are greater among persons aged 50 years and older than among younger persons. The greater HIV diagnosis rates in Blacks and later diagnosis among older persons of all races/ethnicities indicate a need to increase their awareness of risk factors for HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 26 publications
1
56
0
3
Order By: Relevance
“…Failure to request anti-HIV serology during the elderly consultation was also supported by other studies (5,22) . Studies have shown that individuals with 50 years or more were diagnosed at a more advanced stage of the disease, compared to the younger population (22)(23) . However it is clear that the late diagnosis interferes with the prognosis of the disease among the elderly, because in addition to HIV infection, acceleration in the progression of comorbidities among the elderly occurs (2,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to request anti-HIV serology during the elderly consultation was also supported by other studies (5,22) . Studies have shown that individuals with 50 years or more were diagnosed at a more advanced stage of the disease, compared to the younger population (22)(23) . However it is clear that the late diagnosis interferes with the prognosis of the disease among the elderly, because in addition to HIV infection, acceleration in the progression of comorbidities among the elderly occurs (2,22) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, African Americans and Hispanic/Latino Americans comprised 13 % and 16 % of the general U.S. population, but accounted for 43 % and 19 % of people living with HIV/acquired immunodeficiency syndrome (AIDS), respectively. [1][2][3] Racial and ethnic disparities are even more pronounced among older Americans, 4 women, 5 and men who have sex with men (MSM). 6,7 In addition to having disproportionately high prevalence, recent analyses have also suggested that among individuals receiving HIV care, African American patients are less likely to be retained in care 8,9 and to achieve viral suppression in response to antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In elderly patients, diagnosis is being made at a late stage of the natural history of HIV infection, and the test request for HIV only occurs after extensive research and by exclusion of other diseases, which delays the diagnosis and treatment (14)(15)(16) . As many symptoms of the most prevalent diseases in this age group and HIV are similar, to diagnose them separately becomes a complex process.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of specificity of symptoms can delay diagnosis up to 10 months, resulting in delayed antiretroviral treatment (13,15) . It is observed that when compared to younger people, those with 50 years or older who have been diagnosed with HIV are at a more advanced stage of the disease (15)(16) . It is essential that early diagnosis for the elderly occurs as they have a more rapid progression of the disease and/or increased risk of progression because the CD4+ cells fall faster at lower levels, making the immune system more deficient in early treatment.…”
Section: Discussionmentioning
confidence: 99%